Contrasting Phylogeographic Patterns Among Northern and Southern Hemisphere Fin Whale Populations With New Data From the Southern Pacific - Pérez-Alvarez, MJosé; Kraft, Sebastián; Segovia, Nicolás I.; Olavarría, Carlos; Nigenda-Morales, Sergio; Urbán R., Jorge; Viloria-Gómora, Lorena; Archer, Frederick; Moraga, Rodrigo; Sepúlveda, Maritza; Santos-Carvallo, Macarena; Pavez, Guido; et al. (Frontiers in Marine Science, 2021)
Four fin whale sub-species are currently considered valid: Balaenoptera physalus physalus in the North Atlantic, B. p. velifera in the North Pacific, B. p. quoyi and B. p. patachonica in the Southern Hemisphere. The last, not genetically validated, was described as a pygmy-type sub-species, found in low to mid latitudes of the Southern Hemisphere. Genetic analyses across hemispheres show strong phylogeographic structure, yet low geographic coverage in middle latitudes of the Southern Hemisphere impeded an assessment within the area, as well as evaluating the validity of B. p. patachonica. New mtDNA sequences from the Southeastern Pacific allowed an improved coverage of the species’ distribution. Our phylogenetic analyses showed three main lineages and contrasting phylogeographic patterns between Northern and Southern Hemispheres. Absence of recurrent female mediated gene flow between hemispheres was found; however, rare dispersal events revealing old migrations were noted. The absence of genetic structure suggests the existence of one single taxa within the Southern Hemisphere. Thus, until further evidence supporting this subspecies can be produced, such as genetic, ecological, behavioral, or morphological data, we propose that all fin whales from the Southern Hemisphere, including those from middle latitudes of the Southeastern Pacific belong to B. p. quoyi subspecies. This information is important for the current assessment of fin whales, contributing to the evaluation of the taxonomic classification and the conservation of the species.